A genome-wide by PM10 interaction study identifies novel loci for lung function near BICD1 and IL1RN-IL1F10 genes in Korean adults. (April 2020) - Kim, Hyun-Jin; Seo, Yong-Seok; Sung, Joohon; Chae, Jeesoo; Yun, Jae Moon; Kwon, Hyuktae; Cho, Belong; Kim, Jong-Il; Park, Jin-Ho
Abstract: Although several genome-wide interaction studies (GWIS) have been performed in specific European populations to understand the missing link between genetic and environmental factors for lung function, GWIS of Asian samples remain rare. Therefore, we performed a GWIS of exposure to air pollution to identify loci for lung function in Korean adult men. A total of 1826 adult men recruited from two health check-up centers were included in the analysis and the annual mean concentrations of ambient particulate matter with an aerodynamic diameter ≤10 μm (PM10 ) were used. In case of forced vital capacity (FVC), one SNP (rs12312730) that passed our genome-wide threshold of p int < 1 × 10–5 was detected in the intronic region of the BICD1 gene on chromosome 12. In addition, we found two variants (rs6743376 and rs17042888) located near the IL1RN-IL1F10 gene that were involved in the inflammatory response and associated with decreased FVC via interaction with PM10 exposure. A stratified association analysis according to these SNP genotypes showed that PM10 concentrations in subjects with one or two of the risk alleles, compared with those with the non-risk allele, were significantly correlated with a reduction in FVC. This pattern was replicated in another 892 Korean adult samples. The current study reports the first GWIS discovery in an Asian population: the BICD1 and IL1RN-IL1F10 genes may contribute to the decrease in FVC levels by interacting with PM10 exposure. Highlights: Significant interactions between BICD1 or IL1RN-IL1F10 and PM10 for FVC were found. The several SNPs in these genes were more susceptible to FVC decline by PM10 . For FVC, these interaction effects were reproducible in another sample.